Analisis Resiko Operasional dalam Industri Travel Yuk Kita Tour Untuk Meningkatkan Efisiensi dan Kepuasan Pelanggan - Rahmadi Idris Pasaribu; Fajar Agung Leksmana; Yochi Cristhofen Laia; Putri Kemala Dewi Lubis; Rossy Pratiwi Sihombing (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This study aims to investigate the identification, assessment, and control of operational risks in the travel industry, with a focus on PT Yuk Kita Tour. Direct observation and interview methods are used to identify the risks faced by the company. Risk assessment is conducted by considering the likelihood of occurrence and its impact on the company's operations, followed by appropriate mitigation strategies. The analysis results show that risks such as online booking system disruptions, lack of staff training, currency exchange rate fluctuations, regulatory changes, natural disasters, disease outbreaks, transportation delays, and terrorism threats affect operational efficiency and customer satisfaction.To control these risks, PT Yuk Kita Tour implements a comprehensive mitigation strategy, including improved cybersecurity systems, staff training programs, currency hedging strategies, active regulatory monitoring, travel insurance, strict health policies, cooperation with transportation operators, and clear security information to customers. The implementation of these risk control strategies has had a positive impact on the company's performance, with year-on-year increases in revenue and customer satisfaction. This study provides insights into the importance of operational risk management in the travel industry and demonstrates that a proactive approach to risk identification, assessment, and control is possible. This study provides insight into the importance of operational risk management in the travel industry and demonstrates that a proactive approach to risk identification, assessment, and control can improve operational efficiency and customer satisfaction. The practical implication of this study is the importance of continuously monitoring existing risks, adapting control strategies, and involving stakeholders in risk management to ensure sustainable business continuity and superior customer service in a dynamic business environment.